Pengembangan tes diagnostik berbasis web pada materi larutan elektrolit dan nonelektrolit - Putri Hidayah; Zainuddin Muchtar (ARKA INSTITUTE, 2022)
This study aims to determine: the feasibility of web-based diagnostic tests on electrolyte and nonelectrolyte solutions, profiles of students' conceptual understanding after using web-based diagnostic tests on electrolyte and non-electrolyte solutions, chemistry teacher responses to webbased diagnostic tests on electrolyte and non-electrolyte solutions. , student responses to web-based diagnostic tests on electrolyte and nonelectrolyte solutions. The method used in this development research is the ADDIE method which consists of 5 stages of treatment, namely analysis, design, development, implementation and evaluation. The results showed that (1) the developed web-based diagnostic test had very feasible criteria. The percentage of misconceptions on test 1 is 21.67% while test 2 is 33.33%. The percentage of not knowing the concept on test 1 is 61.33% while test 2 is 20%. The percentage of guessing on test 1 is 8% while on test 2 it is 7%. The teacher's response to a webbased diagnostic test on electrolyte and nonelectrolyte solution material obtained the percentage of presentation aspects 92%, language and content aspects 100% and benefits aspects 90%. Student responses to web-based diagnostic tests on electrolyte and nonelectrolyte solutions obtained an average percentage of 83,20% display aspect, 92,60% language and content aspect, and 87,365 benefit aspect.